Foreign and Domestic Divestment and Investment Decisions: Like or Unlike? - Boddewyn, Jean J. (Journal of International Business Studies, 1983)
The managerial literature on foreign investment and divestment is much less developed than the economic literature on foreign direct investment theory. Nevertheless, surveyed with the purpose of better understanding foreign divestment decisions, the research to date reveals some noticeable differences between investment and divestment divisions—whether foreign or domestic—and even more substantial differences between foreign divestment and domestic divestment decisions. Additional research, however, is clearly in order.